Current evidence on the role of lipid lowering drugs in the treatment of psoriasis - Wang, Jiao; Zhang, Shuo; Xing, Meng; Hong, Seokgyeong; Liu, Liu; Ding, Xiao-Jie; Sun, Xiao-ying; Luo, Ying; Wang, Chun-xiao; Zhang, Miao; Li, Bin; Li, Xin (Frontiers in Medicine, 2022)
Background: Abnormal lipid distribution is observed in patients with psoriasis, which increases their risk for atherosclerosis. However, little is known about the relationship between lipid metabolism, psoriasis, and its co-morbidities. Objective: The purpose of this systematic evaluation was to assess the efficacy, safety, and potential mechanisms of action of lipid-lowering drugs for the treatment of psoriasis. Methods: The PubMed, Embase, Cochrane Central Register of Controlled Trials, Clinical Trial, Chinese National Knowledge Infrastructure (CNKI), China Science and Technology Journal Database, and Wanfang Database were searched for relevant articles from inception to December 31, 2021. The RevMan 5.3 and Cochrane risk-of-bias tool were used for data analysis and risk assessment, respectively. The psoriasis area and severity index (PASI) score is the primary outcome indicator in clinical studies. Based on preclinical studies, we elucidated and mapped the action mechanisms of lipid-lowering drugs in the treatment of psoriasis. Results: The study included eight randomized controlled studies, four single-arm studies, and four in vitro studies. The results showed that lipid-lowering drugs, particularly statins, administered both orally and topically, can significantly improve psoriatic skin lesions and reduce the PASI scores (standardized mean difference, (SMD): -0.94; 95% CI: [-1.58, -0.31]; p=0.004). Oral statins performed best at week eight (SMD: -0.92; 95% CI: [-1.39, -0.44]; p=0.0001). The mechanism of lipid-lowering drugs in the treatment of psoriasis may be related to the inhibition of keratinocyte proliferation, inhibition of CCL20–CCR6 interaction, and reduction in the levels of inflammatory factors. Limitations: There are few studies on lipid-lowering drugs and psoriasis, and their small sample sizes may render the evidence unconvincing. Conclusions: The present findings suggest that lipid-lowering drugs are relieving symptoms in psoriasis. Lipid-lowering drugs, particularly statins, can be used to treat psoriasis with good efficacy and few side effects.